A grass-specific cellulose–xylan interaction dominates in sorghum secondary cell walls - Yu Gao (Nature Portfolio, 2020)
Sorghum is a source of lignocellulosic biomass for the production of renewable fuels. Here the authors characterise the sorghum secondary cell wall using multi-dimensional magic angle spinning solid-state NMR and present a model dominated by interactions between three-fold screw xylan and amorphous cellulose.